Indonesian Journal of Social Work Volume 4 Nomor 2 2021: OCIAL SERVICES FOR CHILDREN WITH HIV AND AIDS IN THE COVID-19 PANDEMIC TIME IN YAYASAN LENTERA SURAKARTA - Krisna Dewi Setianingsih; Nono Sutisna (Indonesian Journal of Social Work, 2021)
Surakarta Lentera Foundation is a Child Welfare Institution that provides services for children living with HIV and AIDS. During the Covid-19 pandemic, its services must be adjusted to binding government policies for providing services to children. This study aims to obtain an overview of the actions of the Lentera Foundation management and caregivers in 1) recognizing the threat and risk of the Covid-19 pandemic on children's safety and welfare; 2) developing appropriate protection and care for children during the Covid-19 pandemic; 3) build awareness and self-care of the various risks of the Covid-19 pandemic. This research used a qualitative approach with seven informants, namely the management and caregivers of the Lentera Foundation. Data collection used interviews, focus group discussions (FGD), and observations. The results showed that the services provided by the Lentera Foundation to children with HIV and AIDS were the same as during normal situations, only during the Covid-19 pandemic the administrators and carers had additional duties to take precautions and protect children and residents. Foundation so as not to be exposed to Covid-19. Problems experienced in efforts to protect foster children from the risk of being exposed to Covid-19 are the lack of facilities and infrastructure to comply with health protocols, lack of caregivers both in quantity and quality to assist children to comply with health protocols, online learning, doing time filling activities spare time so that the child does not feel bored during their stay at the Foundation due to social restrictions, the difficulty of children's awareness in adhering to health protocols. Keywords: Social Services, Children With HIV and AIDS, Covid-19 Pandemic